Diversity of stress ranges in cables of cable-stayed bridge due to traffic loads and far-field seismic excitation - Lee, Chong Hoe (2019)
Generally, the analysis of fatigue in bridges places a large emphasis on cyclic live loads in the form of moving traffic and wind loads. However, the rise in seismic activities in the region increases the exposure of steel structures towards additional cyclic loads that could reduce their fatigue life. In this study, the static and dynamic behaviour of a cable-stayed bridge in terms of fatigue of steel elements are addressed by focusing on the stress variation in stay cables due to the effects of moving traffic loads and ground motion excitations. Dynamic responses of the bridge are subjected to moving traffic loads and ground motions considering horizontal and vertical motions from far-field faults. The applied traffic loads are based on Fatigue Load Model (FLM) to produce fatigue damage equivalent to actual traffic. In this study, Fatigue Load Model 4 (FLM4) have adopted as a form of applied traffic load due to its ability to produce a wider range of results with sufficient accuracy. Two forms of traffic configuration will be used: traffic loads in Single Lorry configuration and Convoy Lorry configuration. A suite of three far-field vertical ground motions of varying magnitude has been used. Effects of traffic loads and ground motion on variations of nominal stress in stay cables are presented. The results of this study revealed the notable influence of traffic loads on stress variations of cable-stayed bridges with significant effects due to ground motions scaled to the expected return period. It has been found that stay cables closer to the pylons and side span supports experienced a significantly large stress range when exposed towards traffic loads in Single Lorry configuration due to the localized interaction between the stay cables and narrower load distribution. In contrast, load combinations involving traffic loads in Convoy Lorry configuration resulted in a substantial increase in the maximum stress ranges experienced by stay cables connected to the main span as well as backstays connecting the pylon head to the anchorages near the side span supports. Based on the results, the placement of moving loads in this configuration has a wider spectrum in terms of its effect on the cable-stayed bridge. Moreover, analysis results based on the application of ground motions of different magnitudes have shown that increments to the strength of an earthquake would tend to increase the maximum stress ranges experienced by stay cables throughout the cable-stayed bridge.